1998
DOI: 10.1097/00005537-199807000-00014
|View full text |Cite
|
Sign up to set email alerts
|

A functional anatomic study of the relationship of the nasal cartilages and muscles to the nasal valve area

Abstract: The functioning of the nasal valve area is largely determined by the stability and the mobility of the lateral nasal wall. To gain insight into the kinematics of the lateral nasal wall, we studied the functional anatomy of the nasal muscles and the intercartilaginous and osseous-cartilaginous junctions. We performed gross and microscopic nasal dissection and serial sectioning in 15 human cadaveric noses. In addition, two noses were used for three-dimensional reconstruction of the nasal cartilages. We conclude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 15 publications
0
59
0
3
Order By: Relevance
“…reactivity of th e head of the inferior turbina te that produces the majority of the valvul a r action at this site. 2 By contrast , we b li v that alar flarin g on inspiration is both passive (Bernoulli's principl ) and active (the dilator nar s muscl e). Flaring appears to act to stent the upper lateral cartilag through the intercartilaginous ligaments and will help to stabilize the later l wall of the nose at the Laryngoscope 110: January 2000 178 level of the valve.…”
Section: ~mentioning
confidence: 84%
See 1 more Smart Citation
“…reactivity of th e head of the inferior turbina te that produces the majority of the valvul a r action at this site. 2 By contrast , we b li v that alar flarin g on inspiration is both passive (Bernoulli's principl ) and active (the dilator nar s muscl e). Flaring appears to act to stent the upper lateral cartilag through the intercartilaginous ligaments and will help to stabilize the later l wall of the nose at the Laryngoscope 110: January 2000 178 level of the valve.…”
Section: ~mentioning
confidence: 84%
“…However, it is not influenced by the application of an external splint. 2 Finally, in what we assume was an effort to make the differences obtained look more meaningful than they were, the authors have shown means and standard errors of the means for their data when they should have listed the means and stand ard deviations. In addition they have failed to show that their sample is normally distributed and have thus failed to justify using a parametric analysis.…”
Section: ~mentioning
confidence: 99%
“…The procerus and upper lip elevator muscles and nasal wing have a greater action on facial expression 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Its lateral wall is concave and corresponds to the internal face of the ILC lateral crus, and it is covered by skin with hair and vibrissae. The literature is controversial in terms of nasal muscles function and anatomy 26 . The nasal muscles -nasal dilator muscle, nasal apex muscle, nasal muscle (wing part) and septum depressor muscleaccording to the anatomical description (Chart 1) 26 , have a dilatory function by voluntary contraction of the nostril and the nasal vestibule to increase air flow and in facial expression.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation